The Conditional Nature of Value-Based Proximity Between Countries: Strategic Implications for Mediated Public Diplomacy. (September 2013) - Sheafer, Tamir; Ben-Nun Bloom, Pazit; Shenhav, Shaul R.; Segev, Elad
Media attention accorded to foreign countries constitutes a crucial facet of public diplomacy. Studies have shown that proximity in values is a key factor that determines such media attention. Models of media interest generally assume that the impact of value proximity is universal across countries with different societal value orientations. Yet this study shows that the effect of societal value orientation on media attention to foreign countries is more complex. It is argued here that the societal value orientation in different countries primes different sets of values, which are then applied as a criterion for assessing the importance of foreign states. Our empirical examination is based on the visibility of foreign countries gauged by searching web portals in 57 countries. It shows that in line with our theoretical argument, countries systematically differ in recognizing proximity, such that democracies base their judgment on similarity in shared democratic principles, whereas authoritarian countries focus on the affinity in religious culture. We discuss the strategic implications of this finding for the study of mediated public diplomacy.